Minangkabau Women’s Socio-Economic Adaptation: Living Qur’an Study of Brick-Making Worker in West Sumatera - Bustamam, Risman; Hardivizon, Hardivizon (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
The purpose of this research is to investigate the Minangkabau women’s socio-economic adaptation as the worker of the brick-making in West Sumatera by employing Living Qur’an study approach. This is a qualitative-descriptive research. This research utilizes in-depth interview, observation, and documentation as the data collection techniques and places Minangkabau women who work in the brick-making industry as the research subjects. The research subjects were analyzed based on the social, education, and their economic condition. The research results show that Minangkabau women who work as the brick-making worker come from family with low levels of education and poor economic resources. In fact, the real condition of their job is actually very challenging, with long working hour, extremely hard physical condition, and very low wages. However, they consider this job as a form of devotion to the family and to the husband. They viewed this job is in line with the teaching of the Qur’an in which it is of vital importance for the wife to support her husband in earning a living for the family. The values found in Qur’an such as hard work, patience, and sincerity are implemented into their daily live in both working and personal life contexts. Even though they encountered the economic challenge like income fluctuations and limited access toward health service, they remain firm and try to carry out their role well. In brief, it can be concluded that Minangkabau traditional and religious values are not contradicted to one another and can get a long with the demand of modern economic. In addition, the role of women in informal sector is a form of devotion and responsibility toward family and this role is very well respected. Therefore, intervention of various parties is of needed in order to help improving the welfare of the women who work as the brick-making worker as well as to assure that they are actually working in a more decent and better condition.